Co(III)(salen)-catalyzed phenolic kinetic resolution of two stereocentered benzyloxy and azido epoxides: its application in the synthesis of ICI-118,551, an anti-hypertensive agent - Karabal, Pratibha U.; Kamble, Dayanand A.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2014)
The salen Co(III)-catalyzed phenolic kinetic resolution of racemic anti- or syn-azido and benzyloxy epoxides provides a practical route to a range of enantioenriched anti-or syn-1-aryloxy-3-azido or benzyloxy-2-alcohols in excellent yields and ees. The synthetic potential of this protocol is illustrated with an enantioselective synthesis of ICI-118,551, a beta-blocker, in a highly optically pure form (99% ee).